2011
DOI: 10.1371/journal.pone.0020632
|View full text |Cite
|
Sign up to set email alerts
|

The Motivational Salience of Infant Faces Is Similar for Men and Women

Abstract: Infant facial features are thought to be powerful elicitors of caregiving behaviour. It has been widely assumed that men and women respond in different ways to those features, such as a large forehead and eyes and round protruding cheeks, colloquially described as ‘cute’. We investigated experimentally potential differences using measures of both conscious appraisal (‘liking’) and behavioural responsivity (‘wanting’) to real world infant and adult faces in 71 non-parents. Overall, women gave significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
175
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(189 citation statements)
references
References 43 publications
12
175
2
Order By: Relevance
“…This pattern of results is consistent with the proposal (Parsons et al, 2011;Yamamoto et al, 2009) that infant facial cuteness can have dissociable effects on measures of wanting (i.e., reward) and liking (i.e., ratings).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This pattern of results is consistent with the proposal (Parsons et al, 2011;Yamamoto et al, 2009) that infant facial cuteness can have dissociable effects on measures of wanting (i.e., reward) and liking (i.e., ratings).…”
Section: Resultssupporting
confidence: 91%
“…Studies using behavioral measures of the reward value of faces, such as key-press tasks (Aharon et al, 2001), also suggest that viewing cute infant faces is rewarding; people are willing to expend more effort to view high-cuteness versions of infant face images than they are to view low-cuteness versions (Hahn et al, 2013). This pattern of results has also been observed using unmanipulated infant faces (Parsons et al, 2011;Sprengelmeyer et al, 2013).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Cuter babies were also more likely chosen in the care-taking task. This is in line with findings of Glocker et al (2009a), who reported that cuteness induces caretaking motivation (see also Lorenz, 1943) and with Hahn et al (2013), who found that men and women were more motivated to work to see cute babies (but see Parsons et al, 2011;Sprengelmeyer et al, 2013 for conflicting evidence and a lack of gender difference). The present findings suggest that women might be even more motivated to care for a cute baby around ovulation.…”
Section: Accepted M Manuscriptsupporting
confidence: 89%
“…The authors concluded that female reproductive hormones play a crucial role in cuteness perception. Some research has replicated sex differences regarding cuteness perception, but not its motivational components (i.e., caretaking; Parsons, Young, Kumari, Stein, & Kringelbach, 2011).…”
mentioning
confidence: 99%